Posthuman Commitment: Reframing Core-Level Employee Performance through Organizational Culture in Islamic Banking Institutions - Pratiwi, Retni; Sasmita, Jumiati; Hendriani, Susi; Halim, Edyanus Herman (Journal of Posthumanism, 2025)
In the evolving landscape of posthuman economic systems, where the boundaries between human, machine, and institutional values blur, the role of employee commitment and organizational culture gains renewed importance. This study investigates the determinants of core-level employee performance in Bank Riau Kepri Syariah, emphasizing the moderating role of organizational culture and the mediating role of employee commitment. By integrating behavioral and posthumanist lenses, the study redefines performance metrics in Islamic financial institutions. Using a quantitative approach with SEM-PLS, data were collected from 254 respondents. The results reveal that leadership, job satisfaction, and work environment significantly influence employee performance, with organizational culture strengthening these effects. This research contributes to the reimagining of human resource strategies in posthuman economies and suggests that ethical, culturally embedded human agency remains essential despite increasing automation.